Masons and society in Guatemala, 1871-1903 - Urbina Gaitan, Chester Rodolfo (2023)
This article studies the formation of a Masonic network in Guatemala, its political-economic role in the configuration of Guatemalan society and its main Central American members, registered in the Masonic Registry of the Central American Supreme Council, between the establishment of the liberal revolution of 1871 to the foundation of the Grand Lodge of Guatemala in 1903. The Freemasons studied belonged to the economic, political, military and intellectual elite, not only Guatemalan, but also Central American. They were linked to the state apparatus of their respective countries, since most of them were military, civil servants and lawyers.